Diametral tensile strength of composite resins submitted to different activation techniques Resistência à tração diametral de compósitos resinosos submetidos a diferentes técnicas de ativação - Denise Sá Maia Casselli; Claudia Cia Worschech; Luis Alexandre Maffei Sartini Paulillo; Carlos Tadeu dos Santos Dias (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The aim of this study was to evaluate the diametral tensile strength (DTS) of composite resins submitted to different curing techniques. Four composite resins were tested in this study: Targis (Ivoclar), Solidex (Shofu), Charisma (Heraeus-Kulzer) and Filtek Z250 (3M Espe). Sixty-four cylindrical specimens were prepared and divided into eight groups according to each polymerization technique (n = 8). The indirect composite resins (Targis and Solidex) were polymerized with their respective curing systems (Targis Power and EDG-lux); Charisma and Filtek Z250 were light-cured with conventional polymerization (halogen light) and additionally, with post-curing systems. Specimens were stored in artificial saliva at 37°C for one week. DTS tests were performed in a Universal Testing Machine (0.5 mm/min). The data were statistically analyzed by ANOVA and Duncan tests. The results were (MPa): Z250/EDG-lux: 69.04ª; Z250/Targis Power: 68.57ª; Z250/conventional polymerization: 60.75b; Charisma/Targis Power: 52.34c; Charisma/conventional polymerization: 49.17c; Charisma/EDG-lux: 47.98c; Solidex: 36.62d; Targis: 32.86d. The results reveal that the post-cured Z250 composite resin showed the highest DTS means. Charisma composite presented no significant differences when activation techniques were compared. Direct composite resins presented higher DTS values than indirect resins. O objetivo do trabalho foi avaliar a resistência à tração diametral (DTS) de compósitos submetidos a diferentes técnicas de polimerização. Foram testados quatro compósitos neste estudo: Targis (Ivoclar), Solidex (Shofu), Charisma (Heraeus-Kulzer) e Filtek Z250 (3M Espe). Foram confeccionados 64 corpos-de-prova cilíndricos, que foram divididos em 8 grupos de acordo com a técnica de polimerização (n = 8). Os compósitos indiretos (Targis e Solidex) foram polimerizados com seus respectivos sistemas de ativação (Targis Power e EDG-lux); Charisma e Filtek Z250 foram fotoativados com polimerização convencional (luz halógena) e, adicionalmente, com sistemas de polimerização adicional. Os corpos-de-prova foram armazenados em saliva artificial a 37°C por uma semana. Ensaio de DTS foi realizado em Máquina Universal de Ensaios Instron (0,5 mm/min). Os dados foram analisados estatisticamente pelos testes ANOVA e Duncan. Os resultados foram (MPa): Z250/EDG-lux: 69,04ª; Z250/Targis Power: 68,57ª; Z250/polimerização convencional: 60,75b; Charisma/Targis Power: 52,34c; Charisma/polimerização convencional: 49,17c; Charisma/EDG-lux: 47,98c; Solidex: 36,62d; Targis: 32,86d. Os resultados indicaram que o compósito Z250 polimerizado adicionalmente mostrou os maiores valores de DTS. O compósito Charisma não apresentou diferenças significativas quando foram comparadas diferentes técnicas de polimerização. Compósitos diretos apresentaram maiores valores de DTS que os compósitos indiretos.